'Fines' from the collision of liquid rims. (25th June 2020) - Néel, B.; Lhuissier, H.; Villermaux, E.
Abstract : Abstract : Fines are smaller droplets produced from an auxiliary mechanism besides the formation of the standard drops in a fragmentation process. We report their formation in a controlled experiment which isolates an individual fragmentation protocol: the collision of two rims bordering growing adjacent holes on a liquid sheet. The standard drops come from the capillary breakup of the fused rims. Occasionally, the rims collision is strong enough to trigger a new, splash-like mechanism, producing an expanding lamellae perpendicular to the main sheet, which destabilizes into finer drops. We quantify the threshold condition for the onset of this mechanism first discovered by Lhuissier & Villermaux ( J. Fluid Mech., vol. 714, 2013, pp. 361–392), we document the resulting lamellae dynamics and explain why it affects the mean drop size in the spray, broadening substantially the overall drop size distribution, which we determine. Possible applications of these findings are mentioned.